Reflections of the Relations between Prussian Rulers-Patrons and Authors of Lithuanian Writing in the Dedications of Lithuanian Books of the Sixteenth to Eighteenth Centuries - Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2015)
The author of the article analyses how the prefaces and dedications in the Lithuanian books of Lithuania Minor of the sixteenth to eighteenth centuries reflect the relations between the pioneers of Lithuanian writing and the rulers of the country – the dukes of Prussia whose de facto status was identical to that of a monarch and later of a king. The article presents comparisons of historical sources – rulers’ edicts which promoted the development of writing and education of the Lithuanians, and dedications to rulers in Lithuanian books. It has been established that the authors and editors of Lithuanian books did not compose panegyrics to rulers-patrons: it was the prominent Prussian poets who glorified them with their poetry in various languages. This should be seen as a specific feature of the writing of Prussian Lithuanians.
Keywords: -